2002
DOI: 10.1053/rmed.2002.1328
|View full text |Cite
|
Sign up to set email alerts
|

Serum proinflammatory cytokines and its relationship to clinical parameters in lung cancer patients with reactive thrombocytosis

Abstract: Proinflammatory cytokines Interleukin-1 beta (IL-1 beta) and Interleukin-6 (IL-6) play a significant role in the pathogenetic processes related to various malignant and inflammatory conditions. Leukocytosis, thrombocytosis and increased acute phase protein levels are part of a systemic inflammatory response. In this study, we measured the concentrations of IL-1 beta, IL-6 and ferritin as well as hemoglobin, lactate dehydrogenase (LDH), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) in 23 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
3
25
1
Order By: Relevance
“…Although the specific mechanism underlying development of thrombocytosis in lung cancer patients remains unclear, our results suggest that thrombocytosis does not depend on tumor burden, but instead may represent a biologic phenotype of individual lung tumors. Patients with lung cancer producing bone marrow-stimulating cytokines such as interleukin (IL)-6 [15, 16, 17], IL-1 [15, 17]and macrophage colony-stimulating factor (M-CSF) [18]could exhibit thrombocytosis even at an early stage. Thrombocytosis has been linked with shorter survival in patients with gynecologic cancer [8, 9, 10, 11, 12, 13, 19, 20], renal cancer [8], gastric cancer [14], and lung cancer [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific mechanism underlying development of thrombocytosis in lung cancer patients remains unclear, our results suggest that thrombocytosis does not depend on tumor burden, but instead may represent a biologic phenotype of individual lung tumors. Patients with lung cancer producing bone marrow-stimulating cytokines such as interleukin (IL)-6 [15, 16, 17], IL-1 [15, 17]and macrophage colony-stimulating factor (M-CSF) [18]could exhibit thrombocytosis even at an early stage. Thrombocytosis has been linked with shorter survival in patients with gynecologic cancer [8, 9, 10, 11, 12, 13, 19, 20], renal cancer [8], gastric cancer [14], and lung cancer [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Reactive thrombocytosis in lung cancer has been suggested to be part of the systemic inflammatory reaction for which interleukin-1 beta and interleukin-6 may be intermediate, though not independent, mediators. 13 Thrombocytosis is an independent predictor of poor prognosis in lung-cancer patients. 11,14 Curiously, though, it has not been associated with an increased incidence of venous thromboembolism.…”
Section: Thrombocytosismentioning
confidence: 99%
“…Tumor cells release a series of cytokines that stimulate megakaryocytes and lead to an elevated level of platelets [30]. Studies have confirmed that platelet count has a close relationship with the growth, invasion, and metastases of tumors and the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%